A tale of two hearth sites: Neolithic and intermittent mid to late Holocene occupations in the Jubbah oasis, northern Saudi Arabia. (June 2021) - Guagnin, Maria; Shipton, Ceri; Martin, Louise; Kingwell-Banham, Eleanor; Breeze, Paul; Graham, Lisa; Ott, Florian; Stewart, Mathew; El-Dossary, Sarah; Zahrani, Badr; Al-Omari, Abdulaziz; Alsharekh, Abdullah M.; et al.
Abstract: Hearth sites are characteristic of Holocene occupation in the Arabian sand seas but remain mostly unstudied. Excavations of two multi-period hearth sites in the Jebel Oraf palaeolake basin, in the oasis of Jubbah, now substantially increase our knowledge of these sites. In total, 17 of 170 identified hearths were excavated at Jebel Oraf 2 (ORF2), an open-air site on the edge of a palaeolake. In addition, 11 hearths were excavated at the stratified site of Jebel Oraf 115 (ORF115), a rockshelter formed by two boulders. Radiocarbon dating and lithic assemblages indicate that the majority of these hearths were in use in the second half of the 6th millennium BCE, and that both sites were used sporadically until the recent past. All hearths appear to have been extremely short-lived, and faunal remains suggest they may have been used to cook meat from hunted or trapped wildlife, and occasionally from livestock. The frequent use of grinding stones, often broken into fragments and used to cover hearths is also attested. Evidence for the exceptionally early use of metal from dated occupation deposits as well as from rock art, shows that these short-lived sites were well connected to technological innovations in the wider region.